PEMENUHAN KEWAJIBAN ORANGTUA PENYANDANG TUNAGRAHITA TERHADAP PENDIDIKAN AGAMA ANAK - Supriyanti, Iin; Arifin, Syamsul; Barizi, Ahmad (IAIN PONOROGO, 2024)
The obligation of parents in caring for and educating children is explained in Law number 1 of 1974 concerning marriage, namely in Article 45 paragraphs (1) and (2), also explained in the Al-Qur'an Al-Luqman verses 12-19 concerning the obligations of parents in providing monotheism, faith and morals education to children. Furthermore, what if the obligations as parents are carried out by mentally retarded couples, of course it is different from normal people who are considered to understand state law and are burdened with religious law. Meanwhile, from the data the researchers obtained from 2018 to 2022, there were 7 (seven) cases of marriages of mentally retarded couples in Karangpatihan Village, Balong District, Ponorogo Regency, of course the mentally retarded couple can be said not to carry out their obligations as parents in caring for and educating children like normal people in general. This research is a type of qualitative research with an approach to laws and the Koran. The data collection method was carried out by observation and interviews. The data description method is described descriptively. The purpose of this study is to examine how mentally retarded couples in Karangpatihan Village fulfill their obligations as parents from the perspective of the Marriage Law and Al-Qur'an Al-Luqman verses 12-19 based on the analysis of Ibnu Katsir's interpretation. From the results of the study, parents with mental retardation fulfill their obligations as parents in a way that they can do.